Indigenous Pathways, Transitions and Participation in Higher Education: From Policy to Practice - Steve Larkin; James A. Smith; Jack Frawley (Springer Nature, 2017)
This book brings together contributions by researchers, scholars, policy-makers, practitioners, professionals and citizens who have an interest in or experience of Indigenous pathways and transitions into higher education. University is not for everyone, but a university should be for everyone. To a certain extent, the choice not to participate in higher education should be respected given that there are other avenues and reasons to participate in education and employment that are culturally, socially and/or economically important for society. Those who choose to pursue higher education should do so knowing that there are multiple pathways into higher education and, once there, appropriate support is provided for a successful transition. The book outlines the issues of social inclusion and equity in higher education, and the contributions draw on real-world experiences to reflect the different approaches and strategies currently being adopted. Focusing on research, program design, program evaluation, policy initiatives and experiential narrative accounts, the book critically discusses issues concerning widening participation.
English
Keywords: educational policy and politics; international and comparative education; Higher education